Enhanced isobutanol production using engineered E. coli and B. subtilis host by UV-induced mutation - Kim, Seo Yeong; Choi, Kwon Young (3 Biotech, 2022)
Recombinant Escherichia coli and Bacillus subtilis strains were engineered by simultaneous chemical and ultraviolet-induced random mutagenesis to enhance bio-alcohol production. Our study investigated the bio-alcohol production of six variants of E. coli (EM1–6) and B. subtilis mutants (BM1–6). The induced mutation in the EM variants increased isobutanol (C4 alcohol) production most effectively, whereas pH adjustment and additional l-valine feeding increased isobutanol production by the BM variants. In contrast, pH adjustment or l-valine addition negatively affected isobutanol production by the EM variants. The highest titer of 5.07 g/L of isobutanol from a 40 g/L yeast extract medium (YEM) was achieved by the EM1 variant, whereas 0.57 g/L of isobutanol from YEM supplemented with 5 g/L of l-valine was obtained from the BM5 variant. These results can be applied in further research on engineering production hosts and improving production titers to utilize heterogenous bioresources in the future.